Inherited defects of thyroxine-binding proteins. Issue 5 (October 2015) - Pappa, Theodora; Ferrara, Alfonso Massimiliano; Refetoff, Samuel
Abstract : Thyroid hormones (TH) are bound to three major serum transport proteins, thyroxine-binding globulin (TBG), transthyretin (TTR) and human serum albumin (HSA). TBG has the strongest affinity for TH, whereas HSA is the most abundant protein in plasma. Individuals harboring genetic variations in TH transport proteins present with altered thyroid function tests, but are clinically euthyroid and do not require treatment. Clinical awareness and early recognition of these conditions are important to prevent unnecessary therapy with possible untoward effects. This review summarizes the gene, molecular structure and properties of these TH transport proteins and provides an overview of their inherited abnormalities, clinical presentation, genetic background and pathophysiologic mechanisms.